Enhancing Biodegradability of Textile Wastewater by Ozonation Processes: Optimization with Response Surface Methodology - Ulucan-Altuntas, Kubra; Ilhan, Fatih (TAYLOR & FRANCIS INC, 2018)
In this study, an ozonation process was used to increase biodegradability of textile wastewater by considering chemical oxygen demand (COD) and color removal. Response surface methodology was applied in order to determine the significance of independent variables which are initial pH, reaction time and ozone dose. While a biological oxygen demand (BOD)/COD rate of 0.315 was obtained at optimum conditions, which are pH 9, 75 min of reaction time and 26 mg/L ozone dose, color and COD removal was obtained at 74% and 39%, respectively. BOD/COD ratio value increased from 0.18 to 0.32 by ozonation process. In addition, k coefficient for BOD also increased from 0.21 to 0.30 d(-1).
Keywords: k coefficient; Non-Biodegradable COD; Ozonation; Response Surface Methodology (RSM); BUBBLE-COLUMN REACTOR; ROTATING PACKED-BED; COLOR DEGRADATION; SEMIBATCH REACTOR; OZONE OXIDATION; DIRECT DYE; AZO-DYE; DECOLORIZATION; ELECTROCOAGULATION; EFFLUENTS; Engineering; Environmental Sciences & Ecology